Analisis Hubungan Kekerabatan Jenis Mangga (Mangifera indica L.) Lokal Indramayu berdasarkan Karakter Morfologi Daun - Laila, Fadhillah; Dwimartina, Fina (Universitas Wiralodra, 2025)
Understanding the kinship relationships based on plant morphological traits plays a pivotal role in supporting both conservation efforts and plant breeding initiatives. Such knowledge is particularly beneficial in assisting breeders to identify and select superior parental lines during the breeding process. This study aimed to analyze and provide information on the kinship relationships among several local mango (Mangifera indica L.) varieties from Indramayu by examining their leaf morphological characteristics. The research was conducted using a convenience survey method in mango-growing areas of Jatibarang District, Indramayu, which was presumed to be a secondary center of mango diversity. Morphological data were collected following standardized descriptors from the IPGRI, focusing on local mango varieties including Cengkir, Harumanis, Kidang, Nanas, Bapang, Gedong Gincu, Gajah, Gedong Kagok, Ruca, and Golek. The study was carried out over a three-month period, from January to March 2024. The results revealed the existence of two major clusters among the studied varieties. Based on dendrogram analysis using Jaccard’s similarity coefficient, kinship levels among the varieties range from 0,70 to 0,99, indicating a relatively high degree of genetic similarity. These findings provided baseline data for local mango germplasm characterization and served as a valuable reference for future parental selection in breeding programs.